"Perfection in a Finite Task": Theme and Form in Representative Poems of Richard Wilbur - Wai, Kwok-man Isabella (My University, 1980)
While there has been much helpful commentary on Richard Wilbur's work, inadequate attention has been given to the individual words and phrases which are vital to the entirety of each poem. Critics tend either to propose very specific but limited views of Wilbur's intentions and techniques or to give somewhat sketchy analyses of the individual poems. In this thesis, I have attempted to deal with the bulk and variety of Wilbur's poetic output, especially points of interest and difficulty which critics overlook or tend to skim past.
The five themes discussed in this thesis are related to Wilbur's idea of happiness. A happy poet does justice to the world he perceives. The "world" that Wilbur is concerned with includes the "Republic of Letters," the world of phenomena, and the world of human experiences. An artist continues and modifies his literary tradition and tries to shape the protean diversity of human consciousness. True "happiness" can only be gained through self exposure to life's endless contradictions and through maintaining a balance between the artist's conflicting responses to these contradictions.
One of the many contradictions is the conflict between human vision and the multifarious world. Wilbur attempts to show that physical vision is allied to moral vision. The poet also tries to articulate a compromise between the scientific and the artistic modes of perception. Through vision, man may achieve a reciprocal relationship with the world. A poet's vision is to discover the cosmic harmony beneath the apparently fragmented world and, as in a kaleidoscope, to arrange a design which holds the disparate images together.
Wilbur's mundane commitments counterbalance his spiritual yearnings. His remarks about Robert Frost's Apple-picker--who 11 has climbed not to heaven but toward it, seeking perfection in a finite task11 --provide the key to the understanding of Wilbur's work in general. Corresponding to the rival claims of spirituality and corporeality, the structure of poems on this topic--and many of Wilbur's poems--is dialectical. The arrangement of the arguments is usually a juxtaposition of the thesis against the antithesis, followed by a synthesis. This dialectical format of ideas can be divided into three categories: polarities and counterpoint, dialogues, and narratives of dilemma.
Another rivalry is that between art and reality. Naked reality motivates the artist to metaphor, and he gives reality form and pattern. The difficulty of this relation arises from the intricacy involved in achieving a "borrowing of the powers" from the real objects. Sometimes Wilbur translates the fugitive events into verbal patterns and sometimes he reshapes other artists' interpretations of life into another art form--a poem.
The qualities that Wilbur cherishes in poetry-grace and lightness, for instance--are qualities essential to a purposeful existence. He is concerned with the tension between the limitations imposed upon man and man's aspirations and achievements within or despite these limitations. Wilbur's Weltanschauung is this-worldly: it seeks out ways of living happily in a fallen world. While Wilbur is genuinely saddened by mortality and mutability, he does not seem to be imaginatively held by them. The reader does not suspect the poet's honesty and seriousness in his exaltation of personal equilibrium and his faith in a basically decent universe. But the reader may sometimes miss a sense of human tragedy. Wilbur's limitations are his temperamental peculiarities which he can hardly be expected to transcend consistently. Given his register, Wilbur is brilliant. By and large, he imagines excellence and is uncommonly successful in his attempt to "make it."
Keywords: representative poems; Richard Wilbur; English; Poetry; Arts and Humanities; English Language and Literature; Arts and Humanities